THE IMPACT OF THE COVID-19 PANDEMIC ON COMPULSIVE BUYING BEHAVIOUR AND ONLINE SHOPPING ADDICTION FOR APPAREL PURCHASING IN MALAYSIA: AN OVERVIEW OF GENERATION Y AND GENERATION Z - Normaziana Hassan; Basitah Taif; Rosita Mohd Tajuddin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The COVID-19 pandemic induced a substantial global shift in consumer behaviour, impacting Malaysia in Southeast Asia. This crisis brought forth trends like remote living, social distancing and amplified digital reliance, reshaping consumer inclinations. A notable outcome is the increased prevalence of compulsive buying behaviour (CBB) and online shopping addiction. This is within apparel purchasing, necessitating a thorough inquiry. These behaviours are typified by their impulsive and excessive nature, leading to detrimental consequences for individuals. This study delves into the extent to which the COVID-19 pandemic has intensified the risk of CBB and online shopping addiction, specifically concerning Generation Y and Generation Z in Malaysia. The research aims to identify and analyse the socio-cultural and psychological determinants underpinning these behaviours. Furthermore, substantial progress has been made in researching the impact of the pandemic on CBB and online shopping addiction among Generation Y and Generation Z in Malaysia. Several research gaps persist, providing valuable directions for future studies and interventions. Employing a quantitative research design, this study focuses on collecting and statistically analysing numerical data to comprehend the scope and patterns of CBB, online shopping addiction, and their association with the COVID-19 pandemic among Generation Y and Generation Z in Malaysia. The findings underscore the positive impact of perceived enjoyment and utilitarian attributes (price, convenience, and health aspects) on online buying attitudes, together with the relationship between personal characteristics and re-patronage behaviour. These generations exhibit favourable attitudes toward online purchases as being straightforward and enjoyable. This research uncovers significant insights into CBB and online shopping addiction amidst the COVID-19 pandemic among Generation Y and Generation Z consumers in Malaysia. The pandemic undeniably catalysed an increase in CBB and online shopping addiction among both generations, affirming the relevance of the stress-relief theory as a coping mechanism during times of emotional strain.